Game Based Zumba Kids Training Model For Early Childhood (6-8 Years) - Susanti, Eva; Nofi Marlina Siregar; Eka Fitri Novitasari (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This research is motivated by the need to improve motor coordination and physical fitness in young children through a fun and interactive approach. The aim of this research is to develop and test the effectiveness of the game-based Zumba kids model in improving physical fitness and gross motor skills in children aged 6-8 years. The research method used is a quantitative research method with an experimental design. This research involved two groups, namely the experimental group who took part in the game-based zumba kids program, and the control group who took part in conventional physical activity. Results: Based on independent t-test calculations using SPSS, it is known that the t value is 15.6 and the 2-tailed significance value is 0.000 < 0.05. This shows that there is a significant difference in scores between the experimental group and the control group so it can be said that there is a significant difference between the control and experimental groups in the game-based zumba kids training model for early childhood 6-8. The conclusion of this research is that the zumba kids model is based on the game and is effective in improving physical fitness and gross motor skills in early childhood. This model can be an attractive alternative to physical education programs in schools and can be applied in various child education settings.